Perlindungan Konsumen Terhadap Sistem Pengembalian Uang Pada Pelanggan di Industri Retail - Meriza Elpha Darnia; Alfani Tiara Azmy; Arifa Fasya; Enjelinda Amelia; Fadhli Maulana; Uli Widiriyani (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
This research aims to understand how the legal regulations regulate consumer protection in the refund system in the retail industry, as well as to find out and understand the legal impact of the customer refund system in the retail industry. This research uses normative juridical methods. For example, buying and selling transactions require a legal medium of exchange, as regulated in Article 2 paragraph (2) of the Bank Indonesia Law which states that "Rupiah currency is a legal means of payment in the territory of the Republic of Indonesia. Research results show that often, replacing change with candy is carried out by business actors in the retail industry on the grounds that they do not have sufficient change or the stock of coins has run out. However, based on Article 7 letter a in the Consumer Protection Law (UUPK), business actors should have the intention good intentions and positive intentions to give the remaining money back to consumers using rupiah as a means of payment. In accordance with Law Number 7 of 2011 concerning currency, the legal means of payment is basically money and not candy or other forms. Article 21 paragraph 2 also explains that rupiah must be used in settling other obligations that require payment in money, and in other financial transactions that occur in the territory of Indonesia. Therefore, traders or sellers who do not comply with these provisions, based on Article 33 paragraph 1 of the Currency Law, can be subject to a prison sentence with a maximum duration of one year and a maximum fine of IDR 200 million.